Evaluating the changes in phytochemical composition, hypoglycemic effect, and influence on mice intestinal microbiota of fermented apple juice. (May 2022) - Wang, Xiaowei; Wang, Yaqin; Han, Mengzhen; Liang, Jingjing; Zhang, Meina; Bai, Xue; Yue, Tianli; Gao, Zhenpeng
Graphical abstract: The effect of Lactobacillus fermentum 21828 fermented apple juice on hypoglycemic and intestinal flora. Highlights: Lactobacillus fermentum 21828 altered the phytochemistry of Aksu apple juice. Fermentation given the apple juice stronger biological activities than unfermented apple juice. Fermented apple juice improved fasting blood glucose and high insulin level in diabetic mice. Fermented apple juice can regulate the metabolism of diabetic mice. Fermented Aksu apple juice altered the intestinal flora of diabetic mice. Abstract: Apples are rich in phenolic antioxidants, which have various beneficial effects on human health. The purposes of our study were to evaluate the effects of Lactobacillus fermentum 21828 fermentation on the phytochemical composition and bioactivity of Aksu ( Fuji ) apple juice (AJ), and to evaluate the hypoglycemic effect of fermented AJ (FAJ) and its effect on intestinal flora. Fermentation altered the phytochemistry and enhanced the biological activity (hypoglycemic and antioxidant activities) of AJ. FAJ improved fasting blood glucose and insulin levels in diabetic mice, regulated blood lipid metabolism, reduced oxidative damage, restored damaged islet cells, and reshaped the intestinal flora of diabetic mice by increasing the relative abundance of Actinobacteria, Bifidobacteria, and Faecalibaculum. The results indicate that FAJ is a fermented product that is rich in bioactive components and has potential hypoglycemic and antioxidant activities.